The Protection of the Financial Interests of the European Union—European Union Requirements and their Implementation by the Central and Eastern- European Countries - Udvarhelyi, Bence; Jacsó, Judit (Criminal Legal Studies: European Challenges and Central European Responses in the Criminal Science of the 21st Century, 2022)
This chapter analyzes the efforts of the European Union to protect its financial interests. The first part of the paper sets out the brief historical development of the criminal law protection of the financial interests of the European Union with particular emphasis on the strengthened and reinforced legal framework provided by the Treaty of Lisbon. The second part focuses on the newly adopted Directive of the European Union on the fight against fraud to the Union’s financial interests by means of criminal law. The third part of the study addresses the implementation of the PIF Directive in Central and Eastern-European countries.KEYWORDS: Treaty of Lisbon, protection of the financial interests, PIF Directive, European Public Prosecutor’s Office, tax evasion, tax fraud, money laundering